Deflection test on different orthodontic wire materials sized 0.016 x 0.022 inches - Harris Gadih Pratomo; Endah Mardiati; Eky Soeria Soemantri; Ida Ayu Evangelina (Majalah Kedokteran Gigi Indonesia, 2018)
The development of technology in orthodontic field produces some orthodontic wires that have different deflection abilities. Loading force is the force needed to place an orthodontic wire in bracket slot (activation). Unloading force is the force produced by an orthodontic wire to move tooth (deactivation). Deflection test with three-point bending technique is a technique that is often used to determine the magnitude of the activation and deactivation force of orthodontic wire. Stainless steel (SS), nickel titanium (NiTi), copper nickel titanium (CuNiTi), and beta titanium (TMA), are the types of frequently used wires. This study aimed to compare loading and unloading force on the deflection test of SS, NiTi, CuNiTi, and TMA orthodontic wires sized 0.016 x 0.022 inch on the load-deflection graph. This is a laboratoryexperimental research on a total of 16 pieces of SS, NiTi, CuNiTi, and TMA orthodontic wires sized 0.016 x 0.022 inches. The group was divided based on the type of material. The deflection test was performed using a universal testing machine with a press speed of 5 mm/minute. Loading and unloading forces were recorded on deflections of 0.5; 1; and1.5 mm. Statistical tests of differences among groups were carried out by ANOVA analysis (p-value ≤ 0.05) and post-hoc analysis with T-test. There were significant differences in the loading and unloading forces recorded on deflections of 0.5; 1; and 1.5 mm; except for deflections of 0.5 mm of the SS and nickel-titanium wires. The wire deflection force fromthe lowest to the highest was CuNiTi wire, nickel-titanium wire, TMA wire, and stainless-steel wire.